The Effect of Profitability on Stock Prices in Manufacturing Companies Food and Beverages Listed on the Indonesia Stock Exchange (2015-2019 Period) - Rosna Nurjanah; Tita Kartika; Sophia Annisa (LPPM Universitas Sebelas April, 2019)
The stock price can be regarded as an indicator of the success of the company's management. Success in obtaining profits will provide satisfaction for rational investors. A fairly high stock price will provide benefits, namely in the form of capital gains and a better image for the company, making it easier for management to obtain funds from outside the company. Therefore, every company that issues shares must pay attention to its share price. Stock prices that are too low (underprice) often mean that the company's performance is not good. However, if the stock price is too high (overprice) it can reduce the interest of investors to invest. This study was conducted to determine whether there is a significant effect of the Return On Assets (ROA) variable on stock prices in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population that is the object of this research is manufacturing companies in the food and beverage sector on the Indonesia Stock Exchange for the 2015-2019 period, which were taken by purposive sampling and based on the specified criteria, the number of samples was 7 companies that met the criteria. Based on the results of hypothesis testing obtained t table 1.690. Then 1.842 > 1.690 and 0.003 > 0.05 which indicates that Ha is accepted (H0 is rejected). Thus it can be interpreted that the profitability variable (X) has an effect on the stock price variable (Y).